Anatomy of Green Grief: Reading Ecological and Social Wounds in the Short Story "Ketika Pohon itu Masih Mekar” - Wijaya, Guntur Sekti; Lestari, Erawati Dwi (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This research is motivated by the growing global awareness of environmental issues and the limited number of ecocriticism studies on contemporary Indonesian literary works. The short story Ketika Pohon Itu Masih Mekar by Doni Jaya was selected as the object of this study because it strongly represents the complex relationship between humans and nature through the symbolism of the cincau tree within the framework of a touching family story. The main problem raised is how the representation of the human-environment relationship is depicted in the short story and how nature is positioned not merely as a backdrop but as a central subject of the narrative. This study employs Cheryll Glotfelty's ecocriticism theory, which examines the reciprocal relationship between literature and the physical environment. The method used is descriptive qualitative with a library research approach, in which the researcher conducts a close reading of the short story text and explores various theoretical sources. The findings reveal three layers of ecological relations within the short story: first, a relationship characterized by the attitude of contemplation (tafakur) demonstrated by the character Mother toward the tree; second, an exploitative relationship represented through the cutting of roots and the plundering of leaves; and third, a tragic relationship in which Mother's effort to save the tree ends with her death, which simultaneously signifies the symbolic death of the family's central foundation. This short story serves as an educational medium, conveying that caring for nature is as important as maintaining family bonds.